(untitled) (Revista Tópos, 2013)
O estudo de arqueologia nas áreas dos Sítios Arqueológicos Itatiba e Itatiba II tiveram por objetivo a obtenção de informações sobre os processos culturais, abrangendo as populações indígenas e as frentes pioneiras da sociedade brasileira, evidenciadas na cultura material contida nos registros arqueológicos, incorporando-os à memória regional e nacional, evitando as perdas dessas informações. O presente artigo tem como objetivo apresentar os resultados da pesquisa arqueológica realizada com o material lítico e cerâmico dos Sítios Itatiba e Itatiba II. Palavras-chave: sítio arqueológico histórico, patrimônio cultural, cerâmica histórica, lítico. HISTORIC SITES ITATIBA AND ITATIBA II: INTERPRETATION OF RECORDS FROM LITHICS AND CERAMICS Abstract The study of archaeology in the areas of the Archaeological Sites Itatiba and Itatiba II has aimed to collect information on cultural processes, comprehending the Indian population and the pioneer groups of the Brazilian Society, shown by the cultural material contained in the archaeological records, and also incorporating them into the regional and national memories in order to avoid the loss of such information. The current article aims to present the results of the archaeological research carried an with the lithic and ceramic material of the Sites Itatiba and Itatiba II. Keywords: historical archaeological site, cultural heritage, historic ceramics, lithic.